Parker, M. (2018). Shut down the business school. What’s wrong with management education. London, England: Pluto Press. (Journal of Applied Learning and Teaching, 2018)
The book’s hyperbolic title caught my attention as somebody who is involved in business and management education. As the title suggests, Parker’s work is admittedly polemical rather than a detailed analysis (xiii). One could be tempted to dismiss a book with such a seemingly exaggerated title as a marketing ploy to sell books by the droves, with the purpose being to enrich both author and publisher. But Parker’s book offers a serious, yet humorous, evaluation of the history and status quo of the business school, which unsurprisingly, is less-than-favourable.Martin Parker is currently a Professor in the Department of Management at the University of Bristol and thus an insider of the very institution that he so fiercely attacks (he is well aware of the irony that he bites the hand that feeds him (15)). Professor Parker is a prolific writer, and this book is the most recent in a series of four books that explore alternatives to the current business school models as well as alternative forms of organisation. (The previous three publications of this tetralogy are Against Management (2002), The dictionary of alternatives (2007) and Companion to Alternatives (2014).